From the Dual Character of Chemistry to Practical Realism and Back Again: Philosophy of Science of Rein Vihalemm. - Müürsepp, Peeter; Bekenova, Zhumagul; Nurysheva, Gulzhikhan; Usenov, Galymzhan (Problems / Problemos, 2019)
The focus of the paper is on Rein Vihalemm’s novel approach to science called practical realism. From the perspective of Vihalemm, science is not only theoretical but first and foremost a practical activity. This kind of approach puts chemistry rather than physics into the position of a typical science as chemistry has a dual character resting on both constructive-hypothetico-deductive (ϕ-science) and classifying-historico-descriptive (non-ϕ-science) types of cognition. Chemists deal with finding out the laws of nature like the physicists. However, in addition to this they deal with substances or stuff that is rather an activity typical to natural history. The analysis of the dual character of chemistry brings about the need to analyse philosophically the reasons why physics has held the position of the only science proper so far. The comparative analysis of physics and chemistry at the basis of practical realism suggests that it is chemistry rather than physics that should hold a special position among sciences. Perhaps we should exchange ϕ-science for χ-science.